2016
DOI: 10.1155/2016/9375091
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Biomicroscopy Comparison ofAb InternoandAb ExternoIntraocular Lens Scleral Fixation

Abstract: Purpose. To compare ab interno and ab externo scleral fixation of posterior chamber intraocular lenses (PCIOL) using ultrasound biomicroscopy (UBM). Methods. Randomized patients underwent ab externo or ab interno scleral fixation of a PCIOL. Ultrasound biomicroscopy was performed 3 to 6 months postoperatively, to determine PCIOL centration, IOL distance to the iris at 12, 3, 6, and 9 hours, and haptics placement in relation to the ciliary sulcus. Results. Fifteen patients were enrolled in the study. The ab ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Similar studies in the literature have compared other techniques of IOL fixation. In 2016, Horiguchi et al [16] compared the ab interno and ab externo IOL scleral fixation techniques, which are both variants of the sutured transscleral fixation, and concluded that both techniques achieved similar results in haptic placement, but the ab externo technique was associated with greater vertical tilt. In 2018, Chantarasorn et al [17] compared reinforced scleral fixation using double sutures and intrascleral IOL fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies in the literature have compared other techniques of IOL fixation. In 2016, Horiguchi et al [16] compared the ab interno and ab externo IOL scleral fixation techniques, which are both variants of the sutured transscleral fixation, and concluded that both techniques achieved similar results in haptic placement, but the ab externo technique was associated with greater vertical tilt. In 2018, Chantarasorn et al [17] compared reinforced scleral fixation using double sutures and intrascleral IOL fixation.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that a severe tilting of the IOL caused a significant amount of ocular coma-like aberrations, and that there was a significant positive correlation between the IOL tilt and the coma-like aberration. Horiguchi and associates [ 14 ] also reported a tilting of the IOLs after ab interno and ab externo transscleral fixation by ultrasound biomicroscopy. In our study, the tilt aberrations of the VA-60BBR and VA-70 AD IOLs increased significantly with the extensions but the tilt aberration of the X-60 and X-70 IOLs did not increase.…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] UBM has been used in IOLs patient assessment (nonsutured and sutured fixation of IOL) measuring anterior chamber depth, sulcus-to-sulcus diameter, capsular bag thickness, capsular bag diameter, ciliary ring diameter, ciliary process-capsular bag distance, ciliary apex-capsular bag plane, IOL tilting, haptic location, iris-IOL contact, vitreous incarceration, and conducting a scleral fixation assessment. [ 44 45 ]…”
Section: Ultrasound Biomicroscopymentioning
confidence: 99%